Question
upstudy study bank question image url

Solve the equation. \( \begin{array}{lll}\text { 1) } \frac{4}{2 x}=\frac{5}{x+6} & \text { 2) } \frac{x}{2 x+7}=\frac{x-5}{x-1} \\ \text { 3) } \frac{x^{2}-3}{x+2}=\frac{x-3}{2} & \text { 4) } \frac{3}{2}+\frac{1}{x}=2 \\ \text { - } & \\ \text { 5) } \frac{2}{x-3}+\frac{1}{x}=\frac{x-1}{x-3} & \text { 6) } \frac{6 x}{x+4}+4=\frac{2 x+2}{x-1}\end{array} \)

Ask by Griffiths Mitchell. in the United States
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**Solutions to the Equations:** 1. **Problem 1:** \( x = 4 \) 2. **Problem 2:** \( x = 7 \) and \( x = -5 \) 3. **Problem 3:** \( x = 0 \) and \( x = -1 \) 4. **Problem 4:** \( x = 2 \) 5. **Problem 5:** \( x = 1 \) 6. **Problem 6:** \( x = 2 \) and \( x = -\dfrac{3}{2} \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Extra Insights

Alright, let’s dig into solving these equations with flair! 1) For \( \frac{4}{2x}=\frac{5}{x+6} \), we can cross-multiply to get \( 4(x + 6) = 10x \). Expanding gives \( 4x + 24 = 10x \). Rearranging yields \( 6x = 24 \), so \( x = 4 \). 2) Solving \( \frac{x}{2x+7}=\frac{x-5}{x-1} \) starts with cross-multiplying to get \( x(x - 1) = (x - 5)(2x + 7) \). Expanding goes as follows: \( x^2 - x = 2x^2 + 7x - 10x - 35 \) leading to \( x^2 - x = 2x^2 - 3x - 35 \). Rearranging gives \( 0 = x^2 - 2x - 35 \), which factors into \( (x - 7)(x + 5) = 0 \), thus \( x = 7 \) or \( x = -5 \). 3) For \( \frac{x^2 - 3}{x + 2}=\frac{x - 3}{2} \), cross-multiplying gives \( 2(x^2 - 3) = (x - 3)(x + 2) \) which expands to \( 2x^2 - 6 = x^2 + 2x - 3x - 6 \). Rearranging yields \( x^2 + 3x = 0 \), so factoring gives \( x(x + 3) = 0 \), hence \( x = 0 \) or \( x = -3 \). 4) For \( \frac{3}{2}+\frac{1}{x}=2 \), subtract \( \frac{3}{2} \) from both sides leading to \( \frac{1}{x} = 2 - \frac{3}{2} = \frac{1}{2} \). Inverting gives \( x = 2 \). 5) In \( \frac{2}{x - 3} + \frac{1}{x} = \frac{x - 1}{x - 3} \), we can combine the left side to a single fraction: \( \frac{2x + (x - 3)}{x(x - 3)} = \frac{x - 1}{x - 3} \). Cross-multiplying yields \( (2x + x - 3)(x - 3) = (x - 1)x \). After expanding and rearranging, you can solve the ensuing polynomial. 6) Finally, \( \frac{6x}{x + 4} + 4 = \frac{2x + 2}{x - 1} \) can be rewritten as \( \frac{6x + 4(x + 4)}{x + 4} = \frac{2x + 2}{x - 1} \). This can be solved similarly by cross-multiplying and others as needed to find \( x \). Don’t forget to check for extraneous solutions and restrictions on variables to keep your answers valid! Happy solving!

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy